Mezőgazdasági termelékenységi vizsgálatok - Balogh, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
.Our study examines the territorial productivity of agriculture and the productivity of agricultural work. The methodology of the research did not raise particular questions, whereas the collection and selection of data serving as the basis for the calculation did. After careful consideration, the Eurostat data were taken as the basis, with regard to the requirements of international comparison, too. As a result of the research it was found that the productivity of Hungarian agriculture is low concerning both indices. The figures show that it is found in the group of Member States which joined in 2004 and in 2007 in spite of the well-known fact that until 1990 Hungary was much ahead of those.